Local crime and early marriage: Evidence from India - Sudipa Sarkar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper analyses whether living in a locality with high crime against women affects the probability of early marriage-that is, marriage before the legal age of marriage of girls. We hypothesize that parents who perceive themselves to live in a high-crime locality would marry their daughters off at an early age to protect the chastity of their daughters from any sexual violence. However, there would be no similar effect of perceived crime in the locality on the marriage of sons. Using a nationally representative longitudinal data set and tackling the potential endogeneity of local crime rates, we find evidence to support our hypothesis. The results show that perceived crime against women in the locality significantly increases the likelihood of early marriage of girls, while there is no such effect on boys of comparable age group. We also find no such effect of gender-neutral crimes (such as theft and robbery) on the likelihood of early marriage of girls. Moreover, we find that the relationship holds only in conservative households where the purdah system is practised, and also in the northern region of India, where patriarchal culture and gender norms are stronger than in the southern region. These findings are relevant as under-age marriage has negative consequences for the well-being of women in terms of health, education, post-marital agency, and future economic participation.
Keywords: J12; J13; J16; 330; crime; early marriage; gender; India